2018
DOI: 10.1002/jbm4.10040
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative Evaluation of Muscle Repair by Diffusion Tensor Imaging in Mice

Abstract: Muscle injury is one of the most common traumas in orthopedic and sports medicine. However, there are only a few treatment options with marginal clinical benefits for this condition. Muscle repair after injury involves multiple and complex processes, such as the inflammation phase, regeneration phase, and remodeling phase. To develop a treatment modality and to examine the efficacy of novel interventions and agents for patients with muscle injuries, it is essential to establish a reliable and sensitive method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Hence, the skeletal muscle is anisotropic. When the skeletal muscle is damaged, the diffusion of water molecules inside and outside the skeletal muscle cells changes; the oedema of the interstitium affects changes in DTI parameters such as ADC and FA values, reflecting anisotropy [ 18 , 36 ]. Our study found that the ADC values increased at 0.5 h after eccentric exercises, peaked at 24–48 h, and then declined; the trend of FA values was the opposite of that of ADC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the skeletal muscle is anisotropic. When the skeletal muscle is damaged, the diffusion of water molecules inside and outside the skeletal muscle cells changes; the oedema of the interstitium affects changes in DTI parameters such as ADC and FA values, reflecting anisotropy [ 18 , 36 ]. Our study found that the ADC values increased at 0.5 h after eccentric exercises, peaked at 24–48 h, and then declined; the trend of FA values was the opposite of that of ADC.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion tensor imaging (DTI) is a technology to quantitatively evaluate diffusion anisotropy of water molecules from multiple directions, which can provide information on the organisational proliferation and direction of the fibre bundles [ 16 , 17 ]. Currently, DTI has been widely used in the field of study of the skeletal muscle and the nervous system [ 18 , 19 ]. T2 mapping can reflect specificity through the detection of transverse magnetisation attenuation of tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, because the skeletal muscle cell diameter is larger than the central nervous system cell diameter [41, 42], a diffusion time setting different from that of the nervous system is mandatory [33, 43]. However, during DWI of the skeletal muscles, a short diffusion time similar to that for the central nervous system is often used [1015]. As the skeletal muscles have short T2 values and a long TE cannot be set, it is difficult to utilize a diffusion time suitable for the skeletal muscles from the viewpoint of SNR with the pulsed-field gradient spin-echo method.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies using diffusion-weighted imaging (DWI) for assessing muscles, especially diffusion tensor imaging (DTI) [1014], have been reported. Various factors, such as sex [11], muscle macro-morphological structure (parallel muscle or bipennate muscle) [11], and age [15], can affect DTI values.…”
Section: Introductionmentioning
confidence: 99%
“…The sample temperature during the scan was controlled and maintained at 24°C, similar to that in our previous DWI reports. 20,24 The detailed protocols are presented in Table 1. Because the IVD is large (diameter: 3-4 mm thickness: 1 mm) enough for pixel resolution (100 µm × 100 µm)/slice thickness (sagittal: 1000 µm) ( Figure 1B) and relatively nonanisotropic tissue, we considered the influence of partial volume effects to be small.…”
Section: Mri Protocolmentioning
confidence: 99%